'Let's get this thing open': The pleasures of unboxing videos. (August 2020) - Mowlabocus, Sharif
Digital videos depicting the unboxing of new objects have become a lucrative revenue stream in the YouTube economy and are beginning to attract critical interest from media scholars. Much of this work focuses on the economic and regulatory dimensions of this new digital form, but little has been written regarding the texts themselves or the pleasures they offer viewers. In this article, I contribute to recent scholarship on YouTube genres, by performing a critical 'unboxing' of this digital form. Following a brief introduction to this phenomenon, in which I outline the key narrative tropes found in these videos, I unpack the affective intensities and tactile pleasures that structure these texts, in order to consider how and why unboxing has become so popular.